Barriers and facilitators to integrating antimicrobial stewardship into clinical governance and practice: A Thai case study - van Gulik, Nantanit; Hutchinson, Ana; Considine, Julie; Driscoll, Andrea; Malathum, Kumthorn; Botti, Mari (International Journal of Infection Control, 2020)
Thailand is currently facing the emergence of antimicrobial resistance. To address this issue the Thai government has supported the introduction of antimicrobial stewardship (AMS) programs. Little is known about the perceptions of key-stakeholders regarding the current clinical governance of AMS and the barriers and facilitators to embedding AMS into clinical care. The aim of this study was to explore organizational leaders’ and clinical nurses’ perceptions of the AMS clinical governance structure and activities at a tertiary referral centre in Thailand. Semi-structured interviews and focus group discussions were conducted with 15 organizational leader interviews and three focus groups involving 18 nurses. Four themes emerged from the data: (1) executive seemed to endorse but not support AMS activities; (2) lack of AMS policy and resources to optimize antibiotic prescribing, tracking and reporting; (3) lack of multidisciplinary engagement in the AMS team; and (4) lack of clinician expertise and education about AMS is a major hurdle. Key issues identified included: the need to develop and embed formal AMS policies; the need for organizational investment in personnel, information management systems, and staff education; and the need to establish a multidisciplinary approach to AMS with identifiable roles and responsibilities for each member of the team.